Literature Review: Pemanfaatan Jenis-Jenis Syzigium di Indonesia - Ajeng Mudaningrat; Betty Shinta Indriani; Naila Istianah; Amin Retnoningsih; Enni Suwarsi Rahayu (Jurnal Biologi dan Pembelajarannya (JB&P), 2023)
Syzygium is one of the flora from the Myrtaceae family which is used by Indonesian people in various ways. This article is structured to analyze the various roles of the Syzygium species. The method used in preparing this article is a study of literature from various reputable international journals. Several types of Syzygium discussed in this article are S. jambos, S. fibrosum, S. cumini, S. malaccense, S. samarangense, S. densiflorum, S. grande, S. aromaticum and others. Plants belonging to the Syzygium have various roles including as a food ingredient, a role in agriculture, as a bioremediation agent for polluted environments and as a medicinal ingredient. The role of Syzygium in agriculture includes as a natural pesticide and as a weed control agent. The role of Syzygium in the environmental field is as a bioremediation agent for environments polluted by heavy metals, soil polluted by industrial waste and waterlogged soil with high salinity. Phytochemical compounds found in Syzygium cumini have the potential to be used as medicinal ingredients because they have therapeutic effects because they contain anthocyanins, phenols and polyphenols, compounds that function as antioxidants and anti-inflammatories that function to control oxidative stress in preeclampsia. With this article, it is hoped that the public will be able to find out the various roles of plants from members of the Syzygium so that they can make maximum use of them.